EFFECT OF BLANCHING, RIPENING AND OTHER TREATMENTS ON THE PRODUCTION CHARACTERISTICS OF PECTINOLYTIC ENZYMES FROM BANANA PEELS BY ASPERGILLUS NIGER (Global Journal of Science Frontier Research, 2012)
Three different strains of Apergillus niger isolated from decayed banana peels in Ibadan metropolis, Nigeria depolymerized citrus pectin. The best strain having pectinolytic activity as indicated by the diameter of clear hydrolyzed zone on the medium plates containing commercial citrus pectin as the sole carbon source was selected among the three strains having the largest zone. This isolate was able to produce polygalacturonase and pectin layse enzymes using banana peels (agrowastes) as the sole carbon source. When Solid state fermentation (SSF) and Submerged fermentation (SMF) were carried out with the banana peels as the substrate using the Aspergillus niger with the largest zone, SSF yielded higher level of pectinolytic activity than the SMF. Different treatments of the banana peels used as substrate were carried out by blanching the substrate with cold sodium chloride, treating the banana peels with wood ashes and also allowing the unripe banana to go through ripening stages. Higher yield of pectinases production was obtained when the banana peels were treated compared with when they were not treated at all. Therefore pretreatment of banana peels increases pectinases production.
Keywords: Aspergillus niger; Pectinolytic Activity; Banana peel; Fermentation; Pectinase